PRODUCTION OF HALOGENATED BETA-LACTAM COMPOUND - TORII SHIGERU; TANAKA HIDEO; KAMEYAMA YUTAKA; SASAOKA MICHIO; SUZUKI DAISUKE (1996)
PURPOSE: To obtain the subject compound in high yield and purity in a simple operation by halogenating the allenyl group of an allenyl β-lactam compound using a new halogenating reagent having high site selectivity. CONSTITUTION: A copper(II) halide or metal halide is made to act on the allenyl group of a compound of formula I (R is H or amino; R is H, a halogen, etc.; R is H or a carboxyl group-protecting group; is a hydrocarbon or S-S(O)n -Ar; (n) is 0-2; Ar is an aryl) to obtain the objective halogenated β-lactam compound of formula II (X and Y are each a halogen). The amounts of the copper(II) halide (e.g. cupric chloride) and metal halide (e.g. calcium chloride) to be used are l-10 equivalents based on the compound of formula I, respectively, and the reaction is conducted in a solvent such as N,N-dimethylformamide at -78 to 60 deg.C. The compound of formula II is an important intermediate easily convertible into 3-norcephem, isocephem, etc.